PENDEKATAN REGRESI LOGISTIK BAYES PADA PEMODELAN PERILAKU IBU TERHADAP KEBERSIHAN MULUT ANAK BALITA - SUMAE, KASTIN DWILEN PONG; SRINADI, I GUSTI AYU MADE; SUMARJAYA, I WAYAN (E-Jurnal Matematika; Vol 11 No 4 (2022)DO - 10.24843/MTK.2022.v11.i04.p388, 2022)
Human behavior is a set of behaviors that humans have that are influenced by customs, value, ethics, attitudes, emotion, power, persuasion, and/or genetics. Oral hygiene is a form of dental hygiene. Toddler often suffer from oral and dental problems such as tooth decay or cavities. Hence, parental behavior towards the oral hygiene of toddler is urgently needed. This study aims to determine the factors that significantly influence maternal behavior on oral hygiene in toddler and to obtain a model of maternal behavior using Bayesian logistic regression method. Bayesian method estimation is solved using Markov Chain Monte Carlo (MCMC) simulation. The results of this study indicate that the variables of knowledge and income have a significant impact on maternal behavior in maintaining oral hygiene in toddler.